2022
DOI: 10.2298/apt2253176a
|View full text |Cite
|
Sign up to set email alerts
|

Thermal studies of big sheep horn as thermal barrier coating (TBC) material for gas turbine compressor blade

Abstract: This research focuses on the decomposition temperature of a large sheep horn from Haveri District, Karnataka, India, which is 302.9?C. It also demonstrates the possible use of large sheep horn in the aerospace industry. It can be utilised as a Thermal Barrier Coating (TBC) in high-pressure compressor blades of jet engines. Because of its poor thermal conductivity and specific heat capacity, it is a superb insulator, and temperatures throughout the TBC take around 10 minutes to match.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…More precisely, the hydrophobic protein content in the matrix strongly impacts the glass transition temperature as such proteins could function as internal plasticizers, as for example, in the case of dry wool, which exhibits a 30 °C higher glass transition temperature than dry hair. 34 T g of α keratin obtained with similar moisture content (11%) was reported to be ∼65 °C for wool, 35 ∼ 55 °C for human hair, 34 67 °C for chicken feather 36 (13% moisture), and ∼74 °C for bighorn sheep horn 37 (19% moisture). Another endothermic peak was observed around 175 °C for the horn powder, which corresponded to the denaturation of the keratin.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…More precisely, the hydrophobic protein content in the matrix strongly impacts the glass transition temperature as such proteins could function as internal plasticizers, as for example, in the case of dry wool, which exhibits a 30 °C higher glass transition temperature than dry hair. 34 T g of α keratin obtained with similar moisture content (11%) was reported to be ∼65 °C for wool, 35 ∼ 55 °C for human hair, 34 67 °C for chicken feather 36 (13% moisture), and ∼74 °C for bighorn sheep horn 37 (19% moisture). Another endothermic peak was observed around 175 °C for the horn powder, which corresponded to the denaturation of the keratin.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…38,41 In view of such similarities in thermal behavior, we attribute the water-sensitive keratin denaturation to the melting of the crystalline structure of the horn powder. 37 Thus, we define this point as the lower temperature limit of the processing window. The upper limit to the processing temperature was identified from TGA which revealed that the onset of thermal degradation was at 215 °C for the horn powder (Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations